1996
DOI: 10.1002/(sici)1097-0290(19960405)50:1<1::aid-bit1>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

On the issue of interfacial activation of lipase in nonaqueous media

Abstract: The question of whether lipases can be activated by adsorption onto an interface in organic solvents was addressed using Rhizomucor miehei lipase as a model. In aqueous solution, this enzyme was shown to undergo a marked interfacial activation. However, lipase (either lyophilized or precipitated from water with acetone) suspended in ethanol or 2‐(2‐ethoxyethoxy)ethanol containing triolein exhibited no jump in catalytic activity when the concentration of triolein exceeded its solubility in these solvents, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(8 citation statements)
references
References 24 publications
(1 reference statement)
1
6
0
Order By: Relevance
“…This result suggests that the closing of the lipase lid is caused by water, and the opening of the lipase lid is caused by an oil-water interface in oil-water twophase system. Both closing and opening cannot take place in organic solvents, which agrees with the report that interfacial activation of lipase was caused by an oil (methyl butyrate)water interface, and not by the oil-alcohol interface in a triolein-ethanol two-phase system (21). That is why the activation and inactivation of lipase here was carried out in the presence of an aqueous phase, and the activated lipase had a high activity in organic solvent.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result suggests that the closing of the lipase lid is caused by water, and the opening of the lipase lid is caused by an oil-water interface in oil-water twophase system. Both closing and opening cannot take place in organic solvents, which agrees with the report that interfacial activation of lipase was caused by an oil (methyl butyrate)water interface, and not by the oil-alcohol interface in a triolein-ethanol two-phase system (21). That is why the activation and inactivation of lipase here was carried out in the presence of an aqueous phase, and the activated lipase had a high activity in organic solvent.…”
Section: Resultssupporting
confidence: 91%
“…This revealed that the activated lipase was easily inactivated by water in the absence of an oil-water interface. Derewenda et al (21) reported that the lid of lipase had a high mobility in an aqueous solution and that specific molecular interactions with hydrophobic molecules affected and/or stabilized the lid. There was a subtle equilib-rium between the two conformations (open and closed) of lipase.…”
Section: Resultsmentioning
confidence: 99%
“…From Table , all BCL/MMS‐ x exhibited far higher activity than the non‐immobilized BCL in terms of the conversion of 1‐phenylethanol (C%), and the enantiomeric excess of ( S )‐1‐phenylethanol (ee S ), meanwhile, achieved the same enantiomeric excess of ( R )‐1‐phenylethyl acetate (ee P ), indicating a faster reaction rate. The result can be explained by the following reasons: (a) non‐immobilized BCL got aggregated in the organic solvent, leading to low dispersion and diffusion limitation; (b) during the process of immobilization, hydrophobic isooctane promotes the interfacial activation of the BCL, thus improving its catalytic activity; (c) the large number of mesopores of the MMS‐ x facilitated the mass transfer . These favorable factors make MMS‐ x a very suitable carrier for lipase immobilization.…”
Section: Resultsmentioning
confidence: 99%
“…Immobilization of BCL was conducted according to a procedure described previously, in which BCL was completely immobilized onto magnetic mesoporous silica (MMS‐ x ) via physical adsorption and interfacial activation . First, 0.1 g MMS‐ x was dispersed in 10 mL isooctane in a vessel, and then 0.1 mL 0.1 M pH 6.5 phosphate buffer solution (PBS), which provided “essential water” and pH, was added to the above suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Among different hydrophobic polymers, Ormosils such as alkyl–alkoxysilanes shown better results than the free enzyme counterparts. This behavior of lipases is mainly due to the unique ‘lid’ structure which can be opened while exposing to any hydrophobic interface which facilitates the full expose of the binding site to the substrate . Moreover, the hydrophilic/hydrophobic balance of neighboring surfaces plays an important role in protein structure and biological activity sensitivity and subsequently towards improved structural rigidity.…”
Section: Discussionmentioning
confidence: 99%